70 THE EFFECT OF LEFT VENTRICULAR ASSIST DEVICE THERAPY ON MYOCARDIAL FIBROSIS AND HEMODYNAMIC FUNCTION. (1st March 2006) - Travis, A. R.; Zhou, Z.; Kang, Y. J.; Koenig, S. C.
Abstract : Purpose: Left ventricular assist device (LVAD) therapy has emerged as a viable means for bridging to transplantation in end-stage heart failure patients. There has been conflicting evidence for the effect of this therapy on myocardial interstitial fibrosis, which may play a role in LVAD-induced myocardial recovery. We seek to elucidate the relationship(s) between changes in fibrosis during LVAD support and the following factors: the type of device implanted (continuous vs pulsatile), the duration and mode of support, and the hemodynamic impact of device operation. Methods: Left ventricular pressure, aortic pressure (AoP), aortic flow, and VAD flow waveforms were recorded intraoperatively at the time of LVAD implant and explant. Myocardial tissue samples were obtained from the left ventricle at time of implant and explant. Collagen-stained tissue samples (1 pre- and 1 post-VAD slide for each of three patients) were analyzed for percent fibrosis. All methods were executed as part of an IRB-approved clinical study, with appropriate informed consent of all involved patients. Results: At present, three patients have undergone both LVAD implantation and explantation. Those patients receiving a continuous-flow LVAD (CF-LVAD, n = 2) demonstrated a reduction in percent fibrosis from time of LVAD implant to time of explant, whereas those receiving a pulsatile-flow LVAD (PF-LVAD, n = 1) demonstrated an increase in percent fibrosis. Furthermore, of the two continuous-flow patients, the patient with lower preimplant fibrosis demonstrated a greater reduction in percent fibrosis during the duration of support, evidenced by changes from 4.9 to 2.4% fibrosis and 9.8 to 9.0% fibrosis during LVAD support in these two patients. Hemodynamic recordings indicate a marked reduction in pulsatility of AoP with the CF-LVAD vs the PF-LVAD, which preserves physiological pulsatility. Also, following LVAD support in a CF-LVAD patient, baseline AoP was decreased from pre-VAD status. Conclusions: The type of device and level of preimplant fibrosis may play a role in determining the direction and magnitude of change in myocardial fibrosis due to LVAD support. Moreover, clear differences in the hemodynamic impact of these two devices might reflect an underlying mechanism for the different changes in fibrosis seen with these two device types. In future work, more complete hemodynamic data will be used to calculate indices of function that will be correlated with histological findings in order to strengthen our understanding of the relationship between structural and functional changes brought about by LVAD support.